Как свежи были розы в аду: [роман] / Евгения Михайлова - Михайлова Евгения (Детектив-событие, 2012)
Экземпляры: Аб (20130425) / Инвентарный номер: 99565 / Цена: 177.10 / Авт.знак: М 69 / ББК: 84(2Рос=Рус)6